Three new species of shallow water, yellow zoanthids (Hexacorallia: Zoanthidea: Epizoanthidae) from southern California, USA, and southern Australia - Philipp, Nicholas A.; Fautin, Daphne G. (Zootaxa, 2009)
In southern California and southern Australia, several species of hexacorals that are common at diving depths have been referred to as “Yellow Zoanthids.” We describe three new species of them in the genus Epizoanthus because all have a macrocnemic mesenterial arrangement and mesogleal marginal sphincter muscle. Epizoanthus giveni is from southern California, and Epizoanthus karenae and Epizoanthus rodmani are from southern Australia. Distinguishing features of E. giveni n. sp. are a sphincter muscle with alveoli arrayed in a single, longitudinal column, polyps no longer than 8 mm beyond the coenenchyme, obvious scapus ridges numbering 19 or fewer, and mesenteries numbering 36 or fewer. Distinguishing features of E. karenae n. sp. are radiating dark-orange lines on the oral disc (in life), a broad sphincter muscle filling most of the margin distally and transversely stratified proximally, polyps no longer than 12 mm beyond the coenenchyme, obvious scapus ridges numbering 20 or fewer, and mesenteries numbering no more than 40. Distinguishing features of E. rodmani n. sp. are the lack of lines on the oral disc (in life), a sphincter muscle situated in the middle of the mesoglea with alveoli more elliptical than circular in section, polyps no longer than 8 mm beyond the coenenchyme, scapus ridges not obvious, and mesenteries numbering 48 or fewer.